Early Treatment of Acute Complex Regional Pain Syndrome after Fracture or Injury with Prednisone: Why Is There a Failure to Treat? A Case Series - Paul Winston (Pain Research and Management)
Background. Complex regional pain syndrome (CRPS) after fracture is a cause of pain, dysfunction, and potentially permanent disability. The evidence for treatment with oral corticosteroids is growing and supported by several international guidelines; however, treatment is not widely offered. Objective. Rapid recognition and treatment of complex regional pain in the upper extremity after acute injury as a disease modifying and potentially curative treatment. Methods. The present study was a case series involving three patients who developed CRPS after a trauma to the neck and/or upper limb. Patients were screened by clinical examination and bone scan and met the Budapest criteria. Results. Resolution of pain, swelling, and disability in all three patients. Discussion. There is increasing support, based on the existing evidence and clinical outcomes, for the use of prednisone to treat the acute phase of CRPS and as a promising treatment to halt the progression of the phenomenon and potentially cure the condition; however, widespread use of prednisone likely remains low, potentially resulting in long-term pain, joint contracture, and disability. A large-scale randomized control trial has not been performed. Conclusion. Corticosteroids can be an effective treatment option for CRPS after fracture.